2021
DOI: 10.1021/acs.jpca.1c00483
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Cobalt Clusters Con±/0 with Dinitrogen: Superatom Co6+ and Superatomic Complex Co5N6+

Abstract: We report a joint experimental and theoretical study on the reactions of cobalt clusters (Co n ±/0 ) with nitrogen using the customized reflection time-of-flight mass spectrometer combined with a 177.3 nm deepultraviolet laser. Comparing to the behaviors of neutral Co n (n = 2−30) and anionic Co n − clusters (n = 7−53) which are relatively inert in reacting with nitrogen in the fast-flow tube, Co n + clusters readily react with nitrogen resulting in adducts of one or multiple N 2 except Co 6 + which stands fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Previously published studies based on infrared photodissociation spectroscopy have revealed that the cobalt clusters readily react with N 2 to form Co n N 2 + (n=2–17) [16] . Among the cobalt clusters Co n + (n=2–22), Co 4 + and Co 5 + have been illustrated to exhibit a relatively larger reaction rate with N 2 molecules [14f,17] . However, rare reports showed the formation of odd‐nitrogen cobalt nitrides by far to the best of our knowledge.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previously published studies based on infrared photodissociation spectroscopy have revealed that the cobalt clusters readily react with N 2 to form Co n N 2 + (n=2–17) [16] . Among the cobalt clusters Co n + (n=2–22), Co 4 + and Co 5 + have been illustrated to exhibit a relatively larger reaction rate with N 2 molecules [14f,17] . However, rare reports showed the formation of odd‐nitrogen cobalt nitrides by far to the best of our knowledge.…”
Section: Resultsmentioning
confidence: 98%
“…Figure 3 presents the optimized structures of Co 3,4 N m + (m=0–10) clusters (for details see Figures S3–S5). The nascent Co 3 + has the lowest energy structure of the isosceles triangle while Co 4 + is a tetrahedron [14f,19] . Interestingly, the doping of a single N atom in forming Co 3 N 1 + and Co 4 N 1 + exhibits similar N‐capping on a triangular hollow site; whereas the other odd‐N species Co 3 N 2m‐1 + display significant differences with the Co 4 N 2m‐1 + .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A quantum chemical analysis of the system reveals a particular stable open-shell superatomic structure of D 3d symmetry for Co 6 + causing the low reactivity. 234 The often observed increase of reactivity at low temperature points to the initial formation of a weakly bound molecular complex. This forms the precursor to the activated irreversible dissociation into atomic N on the cluster surface, alternatively molecular N 2 can be released again from the molecular complex.…”
Section: Probing Ligand Binding and Chemistry On Metal Clustersmentioning
confidence: 99%
“…The successful synthesis of such Cu NCs includes Cu 146 Se 73 (PPh 3 ) 30 , 5 Cu 72 Se 36 (PPh 3 ) 20 , 6 Cu 52 Se 26 (PPh 3 ) 16 , 6 Cu 32 Se 16 (PPh 3 ) 12 , 6 some small copper NCs such as Cu 4 NCs, 7,8 Cu 6 NCs, [9][10][11][12][13][14] Cu 8 NCs 14,15 Cu 12 NCs, 16 Cu 13 NCs, 16 Cu 14 NCs, 15,17 Cu 15 NCs, 18 as well as some other copper NCs involving hydrides. [19][20][21][22][23][24][25][26] Among them, the Cu 6 NCs stabilized by various ligands attract the most research interest, such as Cu 6 (MPP) 6 , 14 [Cu 6 (mna) 6 ] 6− , 12 Cu 6 (dmpymt) 6 , 10 Cu 6 (SC 7 H 4 NO) 6 , 13 and Cu 6 (SC 5 H 3 NSiMe 3 ) 6 , 9 allowing such sixatom metal NCs as model systems, [27][28][29][30][31][32][33][34][35] just as Au 25 [SR] 18 , [36][37][38] to fully understand the relationship between structure and property, and to explore stable ones for cluster-genetic materials. [39]…”
mentioning
confidence: 99%